2021
DOI: 10.15416/ijcp.2021.10.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Induced Weight Gain in Schizophrenic Patients

Abstract: Atypical antipsychotics are widely prescribed and have the potential to cause weight gain, which may result in the development of metabolic syndrome. Also, it is important to monitor the use of atypical antipsychotic for metabolic disturbance. The purpose of this study is to determine the side effects of atypical antipsychotics in increasing body weight in schizophrenia patients after 4 weeks of use. Furthermore, a retrospective design was conducted and data were collected based on consecutive sampling in 80 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition, another study explained that the use of atypical antipsychotics for at least four weeks can cause weight gain in patients with schizophrenia and doctors are recommended to monitor metabolic side effects due to the use of atypical antipsychotics. 16 Several factors may alter the microbiome such as infection, disease and diet. Turnbaugh et al 17 demonstrated that switching from a low-fat, polysaccharide-rich diet to a high-fat, high-sugar diet shifts the structure of the microbiota over the course of a day and alters the representation of metabolic pathways in the microbiome, which may occur in hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another study explained that the use of atypical antipsychotics for at least four weeks can cause weight gain in patients with schizophrenia and doctors are recommended to monitor metabolic side effects due to the use of atypical antipsychotics. 16 Several factors may alter the microbiome such as infection, disease and diet. Turnbaugh et al 17 demonstrated that switching from a low-fat, polysaccharide-rich diet to a high-fat, high-sugar diet shifts the structure of the microbiota over the course of a day and alters the representation of metabolic pathways in the microbiome, which may occur in hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, some atypical antipsychotics can stimulate weight gain. In addition, another study explained that the use of atypical antipsychotics for at least four weeks can cause weight gain in patients with schizophrenia and doctors are recommended to monitor metabolic side effects due to the use of atypical antipsychotics [ 16 ].…”
Section: Discussionmentioning
confidence: 99%